Role of the cultural values as a key part in the implementing of healthy practices: Exploratory research (2012)
The healthy organization concept becomes strong in the corporative and academic environments, due to its integral focus and to the impact it has caused in different interest groups. Due to its recent consolidation as a valid concept, there is little to no corpus of investigation about this topic. In order to generate knowledge focused in this concept, an explorative research which aimed to identify the relationship between implementing healthy organizational practices inside organizations and cultural values was developed. To the research, 66 people were given a questionnaire composed of nine variables, five of them based in the Hofstede model (1980) and four more that evaluated the implementation of healthy organizational practices. The result shows that cultural values predict the implementation of healthy practices at the organization. © Common Ground, Merlin Patricia Grueso, Claudia Fabiola Rey, Javier Leonardo Gonzalez, All Rights Reserved.